Additive manufacturing in insoles for the prevention and treatment of diabetic foot ulcer: directional manual (Research, Society and Development, 2023)
Diabetic foot neuropathic ulcers (UPD) precede 85% of amputations and Diabetes Mellitus is the main cause of amputation of lower extremities, the DPU is associated with sensory neuropathy, causing a progressive decrease in sensitivity, the patient may present a clinical picture from: inability to feel pain or discomfort so friction from improperly sized shoes, foreign objects, or injuries caused by stepping on an object with bare feet, can cause ulcers. In this context, this research proposes to describe a directional manual for Additive Manufacturing in insoles for the prevention and treatment of diabetic foot ulcers, promoting a biomechanical adaptation and avoiding major and minor amputations. This is a descriptive study regarding the development of a manual, carried out in the following phases: prior art research, bibliographical surveys, registration of the work in the national library and dissemination in the manual format in e-book format. In addition, the manual is a logistical tool that permeates the development of research and execution of clinical practice.